Diseño e implementación de un sistema de control de estados apertura/cierre de puertas de un refrigerador doméstico 372 LRT F380G TMF empleando tecnología de detección de campos magnéticos. (2023)
This degree work is related to specific objective number 1 of a VCTI2024-1 research project on the real performance of domestic refrigerators. The developed system uses magnetic sensors and signal measurement algorithms to guarantee adequate detection of the change of states of the doors of a domestic refrigerator, considering hardware and software considerations to provide a non-invasive solution. Additional features have been integrated, such as 0° adjustment and remote monitoring through an intuitive user interface and generation of access logs for detailed monitoring. Test and evaluation results demonstrate the effectiveness of the system in terms of reliability when the sensors are located out of reach of other magnetic fields. This technological approach offers a robust and efficient alternative to traditional status control systems, providing greater convenience and control.